Impact of Gene Patents and Licensing Practices on Access to Genetic Testing for Alzheimer’s Disease - Skeehan, Katie (2010)
Genetic testing for Alzheimer’s disease (AD) includes genotyping for apolipoprotein E, for late-onset AD, and three rare autosomal dominant, early-onset forms of AD associated with different genes (APP, PSEN1 and PSEN2). According to researchers, patents have not impeded research in the field, nor were patents an important consideration in the quest for the genetic risk factors. Athena Diagnostics holds exclusive licenses from Duke University for three “method” patents covering APOE genetic testing. Athena offers tests for APOE and genes associated with early onset, autosomal dominant AD. One of those presenilin genes is patented and exclusively licensed to Athena; the other presenilin gene was patented but the patent was allowed to lapse; and one (APP) is patented only as a research tool and patent claims do not cover diagnostic use. Direct-to-consumer testing is available for some AD-related genes, apparently without a license. Athena Diagnostics consolidated its position in the market for AD genetic testing by collecting exclusive rights to patents arising from university research. Duke University also used its licenses to Athena to enforce adherence to clinical guidelines, including elimination of the service from Smart Genetics, which was offering direct-to-consumer risk assessment based on APOE genotyping.